Efektivitas Pemberdayaan Ekonomi Keluarga Tunagrahita dalam Kerangka Sustainable Development Goals di Desa Karangpatihan Ponorogo - Linatul Chariro; Aji Damanuri; Ely Masykuroh (Institut Agama Islam Negeri Ponorogo, 2024)
This research was motivated by the phenomenon of a number of 96 residents in Karangpatihan Village who were mentally retarded or mentally retarded who were still dependent on consumer assistance, making it difficult to fulfill their daily needs. Field research using a qualitative approach. aims: 1) to analyze the implementation of economic empowerment for mentally retarded communities, 2) to analyze the factors inhibiting and driving the economic empowerment of mentally retarded families and the impact of empowerment in increasing the economic income of mentally retarded families, and 3) to analyze the effectiveness of economic empowerment for mentally retarded families in the Sustainable Development Goals concept in Karangpatihan Village, District Balong, Ponorogo Regency. The findings are: 1) Implementation of economic empowerment for mentally retarded families is carried out at the Rumah Harapan Mulya Social Welfare Institution (LKS) by carrying out various activities, such as training, skills and coaching. In implementing empowerment, there are obstacles faced, namely communication and the will of mentally retarded residents. 2) With this training, mentally retarded residents have activities and skills that can generate income. with 3 concepts, namely daily, quarterly and annual. 3) Based on measuring effectiveness using three approaches, namely the goal achievement approach, integration approach, and adaptation approach, the implementation of economic empowerment for mentally retarded families in improving the concept of Sustainable Development Goals in Karangpatihan village is running quite effectively. The existence of empowerment activities has implications for mentally retarded residents, namely: having income, having mobility abilities, and having participation in social life.